An Interview with Dr. Walter Lear - The Editors (Social Medicine Publication Group, 2024)
In this issue of the English version of Social Medicine we are publishing the first of several pamphlets loaned to us by the US Health Activism History Collection. To introduce this collection we travelled to Philadelphia on June 18, 2008 to interview Dr. Walter J. Lear. Dr Lear, born in 1923, is the person responsible for the collection. In a wide-ranging interview in his home Dr. Lear discussed his personal background, the origins and purpose of the collection, the impact of the McCarthy period on the US health left, as well as his vision for the future.